National survey of Australian sonographer knowledge and behaviour surrounding the ALARA principles when conducting the 11–14‐week obstetric screening ultrasound. Issue 2 (May 2016) - Beirne, Geraldene Carruthers; Westerway, Susan Campbell; Ng, Curtise Kin Cheung
Abstract: Objectives: To identify gaps in Australian sonographer's knowledge and application of as low as reasonably achievable (ALARA) principles during first trimester imaging; Identify relationships between demographic variables and knowledge or application of the Output Display Standard (ODS) value thermal index (TI) and compare Australian sonographers to their international peers. Methods: Australian Sonographer Accreditation Registered( ASAR)‐registered sonographers completed a voluntary questionnaire over September 2015 after institutional ethics approval (RDSE‐48‐15). Seventeen questions detailed their demographics (5); knowledge of ultrasound bioeffects terminology and ALARA principles (9); behaviour surrounding ALARA and first trimester imaging (2) and continuing bioeffects education (1). Exclusion criteria was non‐ASAR status. Descriptive (mode frequency) and inferential statistics (Fisher exact test) were used. Significance level was 95%. Results: Ninety‐five valid surveys were collected. Ninety‐nine per cent knew the meaning of ALARA, 93.55% correctly defined 'TI' and 85.39% knew where to find the TI value via the ODS. Half never monitor the ODS. No correlation (P = 0.094) was found between experience and ODS monitoring. No statistical difference (P = 0.189) existed between obstetric and non‐obstetric sonographers who knew the meaning of TIB (87.18% vs. 76.92%) or those who correctly identified it as the setting for 11–14‐week examinations (30.77% vs. 30.77%). When using Doppler during obstetric examinations, no difference existed (P = 0.293), between obstetric and non‐obstetric sonographers' knowledge of ASUM/WFUMB guidelines for maximum TI (47.37% vs. 46.15%). Conclusions: Despite poor ODS usage, Australian sonographers outperform their international peers for ALARA literacy, and show better application of ALARA principles in the first trimester. No relationships were found between demographic variables and knowledge or conscious monitoring of ODS.